Two Years in Crisis — Municipal Finances Remain Sustainable Nonetheless - Florian Boettcher; Ronny Freier (Wirtschaftsdienst)
Abstract Federal and state policies have massively supported the German municipalities during the coronavirus crisis. As a result, municipal budgets in Germany have had a small surplus in 2020 and in 2021. The precise reasons for these surpluses are quite different in both years. In 2020, the additional expenditure as well as the enormous decrease in municipal tax revenue could only be overcome by large spending policies at federal and state level. In 2021, in contrast, the municipalities were back to collecting significant taxes themselves and were mostly self-sustaining. Still, municipal finances in 2021 profited from permanent policy changes regarding the trade tax levy (Gewerbesteuerumlage) and the federal government’s increased co-funding of accommodation costs.